Stabilisation of aluminium foams and films by the joint action of dispersed particles and oxide films. (15th October 2015) - Heim, K.; Vinod-Kumar, G.S.; García-Moreno, F.; Rack, A.; Banhart, J.
Graphical abstract: X-ray radioscopies of AlSi9Mg0.6/SiC/10p foam blown with (a) air and (b) Ar as an injection gas. Both foams were surrounded by air. (c) Ar was used as injection gas and foam was surrounded by Ar atmosphere. The images were taken after stopping bubbling and holding at 680 °C for 600 s. Abstract: Aluminium alloy foams are created by injecting gas containing different levels of oxygen (from ≪1 ppm to 21%) into melts stabilised with SiC or TiB2 particles. Individual liquid aluminium alloy films meant to represent the films in a foam are produced of the same materials. For foams and films, the oxygen concentration of the atmosphere is controlled. Synchrotron X-ray radioscopy on liquid films is applied to track the movements of the particles within and to observe how they flow, pile up and form clusters. Experiments on aluminium foams show that only when the injected gas and the surrounding atmosphere contain oxygen foams can be expanded continuously. In contrast, if foaming is carried out by injecting argon into the melt and the Ar atmosphere is free of oxygen no stable foams can be created, even if the melt contains 20 vol.% SiC particles. Both film and foam surfaces are analysed ex-situ by energy-filtered TEM and SEM. It is found that oxide layers form, cover the particles and push them into the metal. A high oxygen content in combination with Mg in the alloy promotes this process. It is concluded that not only particles are required to allow for foaming, but also the formation of an oxide skin is necessary and the combination of both are the basis of film and foam stabilisation.